Parametrically excited non-linear systems: A comparison of certain methods - Yu, P; Huseyin, K (Pergamon-Elsevier Science Ltd, 1998)
This paper is concerned with bifurcation and stability problems of non-linear systems. The attention is focused on parametrically excited non-linear vibrations. A comparison of C-L method with IHB technique is given on the study of local bifurcations. It is shown that the two methods give qualitatively equivalent bifurcation diagrams. (C) 1998 Elsevier Science Ltd. All rights reserved.
Keywords: Bifurcations; Stability